Comparative Analysis of Teacher Education Systems in Bulgaria, Poland, Russia and Turkey - Necdet Aykac; Hulya Sahin (Educational Process: International Journal, 2018)
The study covers comparative analysis of teacher education systems of Bulgaria, Poland, Russia and Turkey. Russia has a well-established educational system, and both Bulgaria and Poland have made many reforms to their modern teacher educational systems after their European Union membership acceptance and subsequent accession to the EU. Each were selected for this study, and their policies and applications of teacher training, teacher training institutions, conditions of acceptance of students to teacher training institutions, study periods, practicum teaching applications, assignment of teachers to teaching posts, and the status of the teaching profession in these countries were investigated and evaluated by comparing them with Turkey’s current day situation. Therefore, descriptive survey model was used and the research data collected by way of a literature review. While collecting the data, printed academic sources such as theses, books, journals, and articles about the teacher training systems in Bulgaria, Poland, Russia and Turkey have been used. The data attained in this study were evaluated the descriptive analysis approach in terms of the criteria determined in accordance with the aim of the study.